2018
DOI: 10.1016/j.cam.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fractal dimension effectiveness for damage detection in retinal background

Abstract: This work investigates the characterization of bright lesions in retinal fundus images using texture analysis techniques. Exudates and drusen are evidences of retinal damage in diabetic retinopathy (DR) and age-related macular degeneration (AMD) respectively. An automatic detection of pathological tissues could make possible an early detection of these diseases. In this work, fractal analysis is explored in order to discriminate between pathological and healthy retinal texture. After a deep preprocessing step,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…There have been other similar longitudinal studies that found no evidence of an association [ 33 ], and one study found an association between higher arteriolar fractal dimension and diabetic retinopathy [ 35 ]. Using different analysis and computational methods, two recent studies showed the ability of fractal dimension to assist in identification of very early retinal disease [ 36 , 37 ]. Both studies were conducted in people with retinopathy, so prediction was not the aim.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other similar longitudinal studies that found no evidence of an association [ 33 ], and one study found an association between higher arteriolar fractal dimension and diabetic retinopathy [ 35 ]. Using different analysis and computational methods, two recent studies showed the ability of fractal dimension to assist in identification of very early retinal disease [ 36 , 37 ]. Both studies were conducted in people with retinopathy, so prediction was not the aim.…”
Section: Discussionmentioning
confidence: 99%
“…The multifractal nature of the vascular network of the human retina [36, 37] and the reduction of the vasculature complexity with aging [38] have been reported. Fractal analysis has also been used to differentiate between healthy and pathological retinal texture [39].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results of proposed approach are compared with nine existing approaches such as Shabbir et al (), Akram et al (), Kusakunniran et al (), Colomer, Naranjo, Janvier, and Mossi (), Issac et al (), Dashtbozorg, Zhang, Huang, and ter Haar Romeny (), Acharya et al (), and Kaur and Mittal (). Gabor wavelets and Otsu method are applied only for detection of soft‐exudates.…”
Section: Resultsmentioning
confidence: 99%
“…It obtains 95.5% ACC (Akram et al, ). SVM is applied for retinal lesion detection (Colomer et al, ; Issac et al). The supervised based learning method is used for the retinal lesion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation